UPAYA GURU PAI DALAM MENUMBUHKAN KECERDASAN SPIRITUAL SISWA KELAS IX DI SMP NEGERI 2 BANTUR KABUPATEN MALANG - Irma Aprilia; Fathurrahman alfa; Yorita Febry Lismanda (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
The problem currently encountered by globalization in education in Indonesia is the lack of religious knowledge, one of the factor is the indifference of Islam values in the learning process and the lack of students’ morals. The aim of this study is to describe the effort of Islamic Religion teacher in expanding the spiritual intelligence of class IX students at SMPN 2 Bantur Malang, describing the supporting and inhibiting factors to expand students' spiritual intelligence.The research is a qualitative research. The data was collected using observation method, documentation and interviews. In this case, the researcher played a role as a participant and also the researcher was as a planner, executor, data collector, analyzer and reporter on the results of the research. The result of this research showed that the effort of Islamic Religion teacher in expanding the students' spiritual intelligence at SMPN 2 Bantur directed to the formation of morals through religious activities, habit and learning. Religious activities are appreciated so effective because a habit intended as a preparation to strengthen the faith, extend the insights about Islam and created Muslims who are able to filter out the negative influences from the environment and become young generation of morality.